L’Histoire immédiate et son roman - Paul Bleton (Belphégor)
French war fiction (between its WW1 heyday and its petering out in the 80’s) is mostly a fictionalized account of contemporary history — thus, even the very recent past could gain the status of a legitimate and immediately accessible source material for the elaboration of historical narrative. The paper suggests that it is because of this paradoxical extension of the realm of the "past," and the self-contained nature of the war story genre, that many critics were misled. Diagnosing an overall decline in the output of French historical fiction, they missed the point that historical fiction also came in the form of war stories.